Genocide and resistance Nr. 24(2) - Neiburgs, Uldis; Pušinskytė, Lijana; Bubnys, Arūnas; Burauskaitė, Birutė; Rahi-Tamm, Aigi; Lysenko, Aleksandr; Strods, Heinrihs; Vronskaja, Tamara; Polianskaja, Jana; Saueauk, Meelis; Daniel, Aleksandr; Bambals, Ainars; et al. (Genocidas ir rezistencija, 2008)
Full Issue